Granulogorgia amoebosquama, a new genus and species (Octocorallia, Malacalcyonacea, Acanthogorgiidae) from a seamount in the tropical western Pacific - Tang, Rongye; Alderslade, Philip; Xu, Yu; Bilewitch, Jaret P.; Zhan, Zifeng; Xu, Kuidong (Zootaxa, 2025)
Two specimens of the family Acanthogorgiidae Gray, 1859 collected from a seamount on the Caroline Ridge in the western Pacific Ocean are identified and described as a new genus and species using an integrated taxonomic approach. Granulogorgia amoebosquama gen. et sp. nov. is characterized by volcano-shaped calyces and sclerites in the calyx wall consisting of irregular, elongate plates or scales with lobed edges and ornamented with small granules and large warts. The two examined specimens have the same morphological characters and are genetically indistinguishable. Phylogenetic analyses of the mtMutS gene showed a close relationship of Granulogorgia gen. nov. with Pseudoparacis Matsumoto & van Ofwegen, 2023 in the family Acanthogorgiidae. However, Pseudoparacis possesses large thornscales in the calyx wall and large, thick, polygonal plates in the coenenchyme. Granulogorgia amoebosquama gen. et sp. nov. is morphologically most similar to Astromuricea fusca (Thomson, 1911). Unfortunately, no sequence data for Astromuricea Germanos, 1895 are available for phylogenetic analysis. A brief review of that genus is included and it is suggested that the nominal species Astromuricea fusca is likely neither a member of Astromuricea nor Muriceides Wright & Studer, 1889.